Assessment of the Perceptions of Public and Private Partners on their Respective Roles in the building of the Referral Hospital in Lesotho - Mokhutsoane, Thato (2007)
Public Private Partnerships (PPPs) are seen by many as a panacea for all ills of the world. In Lesotho, the use of PPPs to build new public sector infrastructure and deliver public services is a fairly recent phenomenon. The purpose of this study is to assess perceptions and expectations of different stakeholders involved in the procurement of the new referral hospital in Lesotho. Based on findings, I will make recommendations which will be for use by in this project.